Osteocalcin levels decrease during the treatment of an acute depressive episode - Bartečků, Elis; Hořínková, Jana; Křenek, Pavel; Damborská, Alena; Tomandl, Josef; Tomandlová, Marie; Kučera, Jan; Fialová Kučerová, Jana; Bienertová-Vašků, Julie (Frontiers in Psychiatry, 2022)
Objectives: Osteocalcin is a protein secreted by osteoblasts with a versatile endocrine role. Several domains in which it plays a role - stress response, monoamine synthesis, and cognitive functioning - are implicated also in the pathophysiology of major depressive disorder. In search of possible objective biomarkers of depression, the aim of the study was to assess the relationship between osteocalcin and depressive symptoms during the treatment of depressive episode. Methods: The study included female inpatients with at least moderate depressive episode. In these patients, depression severity was measured using the Montgomery-Åsberg Depression Rating Scale (MADRS), and osteocalcin levels were assessed before the stabilization of antidepressive treatment and after six weeks. Relationships between osteocalcin levels and symptoms were analyzed with mixed-effect and linear models, taking into account age, menopausal status, and body mass index. Results: In 11 out of 13 enrolled inpatients, osteocalcin levels decreased during the first six weeks of treatment; this decrease was significant according to the mixed-effects model (t = -2.345, p = 0.019). According to the linear model, this decrease was significantly associated with reduction in depressive symptom severity (t = 2.673, p = 0.028). Osteocalcin was not associated with initial depressive symptom severity, and initial osteocalcin levels did not predict response to treatment. Limitations of the study include low sample size and inclusion of both pre- and postmenopausal women of various ages. Conclusions: This preliminary study suggests that osteocalcin may be a candidate biomarker of antidepressive treatment response and that this topic warrants further investigation.